Activated Spinal Astrocytes are Involved in the Maintenance of Chronic Widespread Mechanical Hyperalgesia after Cast Immobilization. (24th January 2014) - Ohmichi, Mika; Ohmichi, Yusuke; Ohishi, Hitoshi; Yoshimoto, Takahiko; Morimoto, Atsuko; Li, Yuqiang; Sakurai, Hiroki; Nakano, Takashi; Sato, Jun
Background: In the present study, we examined spinal glial cell activation as a central nervous system mechanism of widespread mechanical hyperalgesia in rats that experienced chronic post-cast pain (CPCP) 2 weeks after cast immobilization. Activated spinal microglia and astrocytes were investigated immunohistologically in lumbar and coccygeal spinal cord segments 1 day, 5 weeks, and 13 weeks following cast removal. Results: In the lumbar cord, astrocytes were activated after microglia. Astrocytes also were activated after microglia in the coccygeal cord, but with a delay that was longer than that observed in the lumbar cord. This activation pattern paralleled the observation that mechanical hyperalgesia occurred in the hindleg or the hindpaw before the tail. The activating transcription factor 3 (ATF3) immune response in dorsal root ganglia (DRG) on the last day of cast immobilization suggested that nerve damage might not occur in CPCP rats. The neural activation assessed by the phosphorylated extracellular signal-regulated kinase (pERK) immune response in DRG arose 1 day after cast removal. In addition, L-α-aminoadipate (L-α-AA), an inhibitor of astrocyte activation administered intrathecally 5 weeks after cast removal, inhibited mechanical hyperalgesia in several body parts including the lower leg skin and muscles bilaterally, hindpaws, and tail. Conclusions: These findings suggest that activation of lumbar cord astrocytes is an important factor in widespread mechanical hyperalgesia in CPCP.